ANALISA KEBERAGAMAN (DIVERSTY) TERHADAP IDENTITAS KOTA : Studi Kasus: Koridor Jalan Pemuda, Kota Medan - Iqbal Pulungta Bancin; Hilma Tamiami Fachrudin (Talenta Publisher, 2018)
Urban area will not be separated from the diversity that is owned by the region. A wide variety of diverse elements or objects (buildings, monuments, squares, signs, or the historic old town area, etc.) will give the characteristic features or the identity of a city. The presence of identity on a city course will provide an overview of the place of the region and made the difference with other places. This research was conducted in the road corridor Pemuda, district of Medan Maimun with qualitative methods of observation to the study site for the study using elements of diversity with the aim to discover the diversity of research sites and how with regard to the identity of the city. From the observation there is diversity in terms of different land uses (the function of the building), building typology, activities and others thus creating an identity that can be recognized by the public.